2019
DOI: 10.3389/fpls.2019.00727
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the QTLome of Fusarium Head Blight Resistance in Bread Wheat: Refining the Current Puzzle

Abstract: Background: Fusarium Head Blight (FHB) is a worldwide devastating disease of bread wheat ( Triticum aestivum L.). Genetic resistance is the most effective way to control FHB and many QTL related to this trait have been mapped on the wheat genetic map. This information, however, must be refined to be more efficiently used in breeding programs and for the advance of the basic research. The objective of the present study was to in-depth analyze the QTLome of FHB resistance in bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
167
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(186 citation statements)
references
References 131 publications
17
167
2
Order By: Relevance
“…In the case of the contrasting responding category, we identified neither any cytochrome P450 nor any GT. Interestingly, four genes in the exclusive responding category of DH372 are also identified in wheat and involved in FHB resistance [ 41 ]. Among them, three were identified as P450s and glycosyltransferase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the contrasting responding category, we identified neither any cytochrome P450 nor any GT. Interestingly, four genes in the exclusive responding category of DH372 are also identified in wheat and involved in FHB resistance [ 41 ]. Among them, three were identified as P450s and glycosyltransferase.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, cytochrome P450s are associated with FHB resistance in several earlier studies [ 44 , 67 , 68 ]. The meta-analysis of the QTLome of FHB resistance by Venske et al, 2019, identified 10 candidate genes responsible for FHB resistance in bread wheat [ 41 ]. Among them, three belong to GTs and cytochrome P450.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make these mapped QTL more useful to plant breeding and gene cloning, a further analysis of all these loci has to be carried out. However, due to the fact that most QTL mapping studies differ in numerous aspects, such as mapping population type, and size, and molecular marker type, an elaborated method has to be applied for this purpose (Venske et al 2019). In this regard, meta-analysis of QTL has been proven as an e cient approach, and has been constantly improved (Go net and Gerber 2000; Salvi and Tuberosa 2015), which aims to verify whether QTL in isolated studies actually represent a common position or not on the genetic map of the studied species, and stablish the occurrence of QTL "hotspots" in a consensus map.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, meta-analysis of QTL has been proven as an e cient approach, and has been constantly improved (Go net and Gerber 2000; Salvi and Tuberosa 2015), which aims to verify whether QTL in isolated studies actually represent a common position or not on the genetic map of the studied species, and stablish the occurrence of QTL "hotspots" in a consensus map. This approach was already applied to various crops and complex traits, such as fusarium head blight resistance in bread wheat (Venske et al 2019), grain weight in tetraploid wheat (Avni et al 2018), cist nematode resistance in soybean (Guo et al 2006a), resistance to white mold in common bean (Vasconcellos et al 2017), yield under drought in rice (Swamy et al 2011), yield in maize (Martinez et al, 2016), and multiple traits in cotton (Said et al 2013). (Zhang et al 2019a).…”
Section: Introductionmentioning
confidence: 99%